Predicting Misleading Financial Statement in Malaysia - Nor Afifah, Shabani (2011)
This study aims to examine the ability of financial ratios in predicting misleading financial statements, specifically in Malaysian environment. This study uses nine financial ratios; seven which are commonly used in previous studies (TLTA, NITA, NIS, CATA, RTA, WCTA & STA) and two additional ratios which have never been tested in previous studies (CFOTA & CFOS). Two time periods were studied to compare the usefulness of financial ratios in predicting misleading financial statements for the first year fraud deem to exist and a year prior it comes out clear. Univariate and multivariate such as independent sample test and logistic regression technique were used to analyze the data. Results from univariate test show six financial ratios are significant while results from logistic regression analysis show that three ratios are significant for the misleading year and two ratios for preceding year. NITA is the only ratio that is significant for all three tests conducted. Thus, it is concluded that financial ratios are able to predict misleading financial statements.